International Conference on the “History of World Calendars and Calendar Making” (South Korea, Nov. 29 – Dec. 2, 2016) - Jerzy M. Kreiner (Studia Historiae Scientiarum, 2017)
The article contains short information about the international conference on the history of world calendars and calendar making. The conference was organized to commemorate the 600th anniversary of the birth of Kim Dam (1416–1464), a leading Korean astronomer and calendar scholar. The papers presented at the conference included the interactions among different cultures and regions, and the contributions of astronomers to calendar making.